Peningkatan Komunikasi Interpersonal Siswa Melalui Layanan Bimbingan Kelompok dengan Teknik Role Playing pada Siswa Kelas XI SMAN 2 Kudus - Rustiyawan, Salwaa Azzahra; Lestari, Indah; Hidayati, Richma (SENTRI: Jurnal Riset Ilmiah, 2026)
Interpersonal communication is an essential skill that supports students' social interaction and participation in the learning process. Preliminary observations at SMAN 2 Kudus indicated that several eleventh-grade students demonstrated low interpersonal communication, characterized by limited self-confidence, reluctance to express opinions, low participation in group discussions, and weak empathy toward peers. This study aimed to improve students' interpersonal communication through group guidance services using the role-playing technique. The study employed Guidance and Counseling Action Research (PTBK) conducted in two cycles consisting of planning, implementation, observation, and reflection. The participants were eight eleventh-grade students selected through purposive sampling. Data were collected using questionnaires, observations, interviews, and documentation, and analyzed through descriptive quantitative and qualitative approaches. The findings showed a consistent improvement in students' interpersonal communication. The average questionnaire score increased from 40.5% in the pre-cycle to 60% in Cycle I and 78.75% in Cycle II. Improvements were observed in openness, empathy, supportiveness, and positiveness. Students became more confident in expressing opinions, participated more actively in discussions, demonstrated greater empathy, and showed better cooperation with peers. The findings indicate that group guidance services using the role-playing technique are effective in improving the interpersonal communication skills of eleventh-grade students at SMAN 2 Kudus.